In vivo patch-clamp recordings reveal distinct subthreshold signatures and threshold dynamics of midbrain dopamine neurons - Kanako Otomo (Nature Portfolio, 2020)
The in vivo firing patterns of ventral midbrain dopamine neurons are controlled by afferent and intrinsic activity. The authors identified biophysical membrane potential signatures associated with distinct in vivo firing patterns in whole-cell recordings of spontaneously active midbrain dopamine neurons.